Geotourism and Cultural Heritage - Kerran Olson; Ross Dowling (Geoconservation Research)
Geotourism is often thought to refer solely to ‘geological tourism’, however, more recent views suggest that the term in fact refers much more broadly to encompass not only geology, but also fauna and flora as well as cultural aspects. An area’s geo-heritage can be defined as the geological base that, when combined with climate, has shaped the plants and animals of an area, which in turn determine an area's culture; that is, how people have lived in that area both in the past as well as in the present. This link has rarely been explored in academic literature, so this paper aims to address the way in which geology has shaped Indigenous tourism in Australia. An example of the ways in which the link between geotourism and a place's culture may be misunderstood is given through discussion of Uluru-Kata Tjuta National Park in central Australia, where tourists have climbed Uluru (Ayers Rock) for generations, despite protest from traditional land owners, the Anangu people. Evolving understandings relating to the importance of cultural authenticity in tourism have led to the climbing of Uluru being banned effective from 2019.